Refleksi Etika Mengenai Pengobatan Komplementer dan Alternatif - K. Bertens (Respons: Jurnal Etika Sosial, 2008)
Abstract: When we compare complementary and alternative medicine (CAM) with conventional medicine, the most striking difference is thatCAMis characterised by a broad cultural diversity, whereas conventional medicine is far more unified because of its scientific base. In former times the adverse attitude of conventional medicine towardsCAMwas much stronger than it is nowadays. The reason for this change is that the powerful position of the medical profession came to an end in our more liberal era. But this does not mean that the borderline betweenCAMand the medical profession may be wiped out. It seems ethically questionable when a professional physician turns to CAM practices, as it is also unethical when aCAMpractician appears as a physician.CAMshould be given freedom as long as it causes no harm to the patients.Kata Kunci: Bioetika, Pengobatan Komplementer dan Alternatif, Profesi Medis.